The Selection of Propeller and Primary Engine Matching Level of a 30 GT Fishing Vessel with Analytic Hierarchy Process (Case Study KM Inka Mina 759) - Andi Haris Muhammad; Alfin Thariq; Zulkifli Yusuf; Hartono Yudo; M. Yasir (Department of Naval Architecture - Diponegoro University, 2022)
Reducing fuel consumption and carbon emissions in the development of ship propulsion systems following the required Energy Efficiency Design Index (EEDI) has become a concern for the fishing industry, as determined by the International Maritime Organization (IMO). This study aims to analyze the level of suitability of the use of a 30 GT fishing boat propeller and engine propulsion for optimum propulsion efficiency. The analysis focuses on developing a propulsion system selection model, studying the characteristics of the ship resistance, loading propellers, and selecting the appropriate engine. The engine-propeller matching procedure is used to predict the optimum speed power. Furthermore, the Analytic Hierarchy Process (AHP) method determines the suitability level for the propeller and diesel engine. The results showed the highest level of suitability for the Yanmar 6CH-HHTEC engine versus the A.30X34 type propeller (SP23), with 31.7%. Then the Deutz BF06M1013MC engine versus the B.30X28 propeller type (SP32), the Yuchai YC6A170C engine versus the B30X28 propeller type (SP12), and the Volvo D7ATA engine versus the B30X28 propeller type (SP42) with percentages of 26.6%, 26.4%, and 15.3%, respectively. The high level of SP23 selection is due to the propulsion system having minimal noise levels, dimensions, and engine weight but having maximum power.